Praksisnær forskning - Nielsen, Lene Stumph; Munch, Per; Nielsen, Annegrethe (Tidsskrift for Professionsstudier, 2019)
This article presents and discusses the scientific theory and methodological approaches that have been useful in investigating: a) how the formation of professional identity occurs among bachelor students, and b) what characterizes reflexive practice-based learning, when this learning approach is intended to support student formation processes. Our research design has contributed to establish spaces, where researchers and project participants have been able to explore the phenomena together. The research design has also made it possible to obtain a rich empirical material in order to analyze and understand the reflexive processes and the development of a didactic design aimed to support the student's development of professional identity.